2022
DOI: 10.21203/rs.3.rs-1742161/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TCP1 promotes the progression of malignant tumors by stabilizing c-Myc through the AKT/GSK-3β and ERK signaling pathways

Abstract: TCP1, one of the subunits of molecular chaperone containing tailless complex polypeptide 1 (CCT) (CCT1), maybe play an essential role in cell proliferation and tumorigenesis. However, the biological functions and the underlying mechanisms of TCP1 in tumors are not fully understood. Here, we found that TCP1 levels increased with successive generations of xenografted tumors and were associated with the tumorigenicity of HL-60 cells. TCP1 expression was significantly higher in de novo and recurrent leukemia clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…In recent years, deep neural networks have achieved remarkable success in various computer vision tasks. However, the high computational cost and memory requirements of large neural networks have become a major obstacle to their deployment on resource-constrained devices [2,5,10,25]. Model sparsity is a promising approach to address this issue by reducing the number of parameters in the deep neural network.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, deep neural networks have achieved remarkable success in various computer vision tasks. However, the high computational cost and memory requirements of large neural networks have become a major obstacle to their deployment on resource-constrained devices [2,5,10,25]. Model sparsity is a promising approach to address this issue by reducing the number of parameters in the deep neural network.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the appropriate treatment for DL injury is still controversial in ankle sprains [3,13,16,30]. DL injury in cases of ankle fracture can be treated via conservative management with good results, and no chronic medial instability was observed [6,17,27,28]. On the other hand, it has been shown that concomitant DL repair enhanced ankle stability in an ankle with both syndesmotic and DL disruptions [24].…”
Section: Introductionmentioning
confidence: 99%